Contributions of climatic factors and vegetation cover to the temporal shift in Asian dust events - Wencun Zhou; Huanjiong Wang; Quansheng Ge (npj Climate and Atmospheric Science)
Abstract Asia is one of the largest dust source regions in the world. However, the temporal variations and drivers of different types of dust events in this region remain unclear. Based on surface observation data, we explored spatiotemporal changes in three types of dust events and their driving factors in Asia by using machine learning methods. Results indicated that the frequency of moderate dust events (MDE) and severe dust events (SDE) decreased significantly from 2000 to 2022, which could be primarily attributed to a decrease in strong wind days (contribution >50%), and to a lesser extent to increases in soil moisture, precipitation, and leaf area index (LAI). When the daily maximum wind speed exceeds 13.0 m/s, the probability of MDE tends to decrease, while the probability of SDE tends to increase. These findings enhance our understanding of the variation in frequency and intensity of dust events in response to climate change.